Syngas Generation Process Simulation: A Comparative Study - Reyner P. P. de Oliveira; Maria E. K. Fuziki; Priscila M. L. Z. Costa; Angelo Marcelo Tusset; Giane G. Lenzi (Association for Scientific Computing Electronics and Engineering (ASCEE), 2022)
Methane reforming processes are of great importance for both the reduction of this greenhouse gas concentration in the atmosphere and for hydrogen production for energetic or chemical synthesis purposes. The use of Biogas in substitution for methane in reforming processes still provides a solution for the recovery of organic waste capable of producing Biogas. However, an in-depth analysis of the advantages of this substitution from the point of view of process yield is still lacking. Thus, the main contribution of the present research is the focus given to the comparison between methane and biogas as a reactant for the dry and steam reforming processes. In this work, a computational comparison of syngas production processes was performed, considering the system within the open-loop control. The software Aspen Hysys was used based on the minimization of Gibbs free energy in equilibrium. The parameters studied were: molar ratio of reagents (1-5), temperature (600-1000 °C), and pressure (1-5 bar). Dry methane reforming and steam methane reforming units were simulated, as well as both units using Biogas as a methane source. The plant was built in the simulator, and the results obtained indicated that high values in the molar ratio of CO2/CH4, CO2/Biogas, H2O/CH4, and H2O/Biogas, high temperatures, and low pressures favor the maximum conversion of methane. The use of Biogas in replacement of pure methane in the reform process proved to be advantageous for favoring the synthesis gas production reaction, besides adding value to a residue.